On ?-statistical convergence of difference sequences of fuzzy numbers - Et, Mikall; Altinok, Hifsi; Colak, Rifat (Elsevier Science Inc, 2006)
In this paper the concept of strongly Delta(2)(lambda p)-Cesaro summability of a sequence of fuzzy numbers is introduced. Also some inclusion relations between the set of strongly Delta(2)(lambda p)-Cesaro convergent and Delta(2)(lambda)-statistically convergent sequences of fuzzy numbers are given. (C) 2005 Elsevier Inc. All rights reserved.
Keywords: fuzzy numbers; statistical convergence; difference sequence